IDEAÇÕES E TENTATIVAS DE SUICÍDIO: ATUAÇÃO PROFISSIONAL NA ATENÇÃO PRIMÁRIA - DANIELA BRUNO DOS SANTOS (2023)
Suicide is a frequent problem in Brazil and around the world and, in recent decades, it has become the target of several studies, mainly due to the progressive increase in cases. Coping with this phenomenon also permeates the health field, where the primary level of care emerges as important for mental health care. Thus, the general objective of this study was to characterize and analyze the conceptions and practices of professionals who work in Basic Health Care, focused on care in situations involving suicide ideations and attempts, primarily in health units organized according to the Family Health Strategy, backed by psychologists who are part of teams from the Expanded Center for Family Health and Primary Care (NASF-AB), in Campo Grande/MS. This is a qualitative study. Data collection occurred through semi- structured interviews (two psychologists) and focus groups (two Family Health Strategy - ESF teams, from different health units, one unit with support from one of the psychologists via NASF-AB and the other no), totaling 18 participants. The analyzes are based on the theoretical-methodological assumptions of the method of historical- dialectical materialism in the area of collective health, Historical-Cultural Psychology and Social Psychology in Health. It is expected that the study will contribute with important data and reflections for the understanding of phenomenon and the practice of professionals in the health field as a care strategy in Primary Care.